2023
DOI: 10.21203/rs.3.rs-2682353/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial accessibility of continuous maternal and perinatal healthcare services in Mozambique

Abstract: Maternal and perinatal healthcare remain insufficient in impoverished regions such as sub-Saharan Africa (SSA), and removing geographic barriers to access continuous maternal and perinatal healthcare services (CMPHS) has been addressed as a critical strategy. Based on the framework of maternal, neonatal, and child health (MNCH) proposed by WHO, access to CMPHS in Mozambique was assessed as the integration of three independent service packages, namely antenatal care (ANC), institutional delivery (ID), and postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…11 In Mozambique, Maputo City remains the only province where 100% of the population has access to a health facility within 10km. This finding is similar to several studies which found high access to health facilities in Maputo City, 11,32 this can likely be attributed to the better economic and social development in Maputo City compared to other provinces in Mozambique. Our results demonstrate that access to a health facility is similar to, albeit slightly higher than other countries such as Uganda (71.7%) and Niger (75.0%).…”
Section: Discussionsupporting
confidence: 91%
“…11 In Mozambique, Maputo City remains the only province where 100% of the population has access to a health facility within 10km. This finding is similar to several studies which found high access to health facilities in Maputo City, 11,32 this can likely be attributed to the better economic and social development in Maputo City compared to other provinces in Mozambique. Our results demonstrate that access to a health facility is similar to, albeit slightly higher than other countries such as Uganda (71.7%) and Niger (75.0%).…”
Section: Discussionsupporting
confidence: 91%